2008
DOI: 10.1090/s0002-9939-08-09642-1
|View full text |Cite
|
Sign up to set email alerts
|

On amalgamations of Heegaard splittings with high distance

Abstract: Let M be a compact, orientable 3-manifold and F an essential closed surface which cuts M into M 1 and M 2 . Suppose that M i has a Heegaard splitting, and the amalgamation of V 1 ∪ S 1 W 1 and V 2 ∪ S 2 W 2 is the unique minimal Heegaard splitting of M up to isotopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…to obtain subsurfaces Q In the following, we give an application of Theorem 4.2. Remark The condition in Theorem 4.2 is weaker than that in the main results of Kobayashi and Qiu [6] and Yang and Lei [19].…”
Section: Casementioning
confidence: 90%
See 1 more Smart Citation
“…to obtain subsurfaces Q In the following, we give an application of Theorem 4.2. Remark The condition in Theorem 4.2 is weaker than that in the main results of Kobayashi and Qiu [6] and Yang and Lei [19].…”
Section: Casementioning
confidence: 90%
“…On the other hand, it has been shown that under some conditions on the manifolds, or the gluing maps, the equality g.M / D g.M 1 / C g.M 2 / g.F / holds; see Kobayashi and Qiu [6], Lackenby [8], Lei and Yang [9], Li [10], Souto [18], Yang and Lei [19] and others.…”
Section: Introductionmentioning
confidence: 99%
“…Lemma 2.3 [15]. Let M = V ∪ S W be a strongly irreducible Heegaard splitting and F a 2-sided essential surface (not a disk or 2-sphere) in M .…”
Section: Preliminariesmentioning
confidence: 99%
“…In the papers of Kobayashi-Qiu [4] and Yang-Lei [15], they described a sufficient condition for the equality to hold in term of "high" distance of Heegaard splittings of the submanifolds, see, for example, Theorem 1.3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that under some conditions on the manifolds, the gluing maps, or the distances of the factor manifolds, the equality g(M ) = g(M 1 ) + g(M 2 ) − g(F ) holds, see [9], [10], [20], [7] and [21] etc.…”
Section: Introductionmentioning
confidence: 99%